Transformation of Public Research Institutes’ Role in Indonesia: The Case of Indonesian Institute of Sciences (LIPI) and the Agency for the Assessment and Application of Technology (BPPT) - Purwaningsih, Indah; Kusdi, Kusdi; Amin, Fadillah (Jurnal Ilmiah Administrasi Publik, 2017)
The government of Indonesia has a changing strategy for Science and Technology (S&T) development. This condition has influenced institutional development, which in turn may have affected the transformational role of public research institutes. This study attempts to investigate the trajectory of Indonesian S&T development strategy from the colonial era through the Old Older, the New Order, and following the Asian Financial Crisis. In response to this changing of development strategy, it eventually analyzes how the role of public research institutes has transformed, by takings LIPI and BPPT as case studies. This study employs a historical approach by using interview and document analysis to investigate the trajectory of S&T development in Indonesia and the transformation of LIPI’s and BPPT’s role. The findings suggest that political transformation has much affected the government’s strategy on Indonesian S&T development. Moreover, LIPI and BPPT tend to transform their role following the government’s strategy by giving less consideration to either demand from society and industry or their strong point of early inception.